(3SQGL GdbdhH aj GdJUhas - (3CMeO Hf eMeO Hf YHO Gdedc GdGTYQj GdJHQjRj, CHh GdeMGeOs
(3ChdgG (B:s
(3GdJeS efj HYV ENhGf Cf Cedj cJGH eTJedkG Ydi PcQ ebGeGJ GdYhGe hGdNhGU hSejJg SQGL GdbdhH s
(3BNQgG (B:s
(3HGdEWdGY Ydjg SaQ GdMb Je cJGH SGL GdbdhH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B983s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs